Graphene dispersion liquid and method for producing the same

By mixing graphite with organic acid salt and grinding, forming a composite, and mixing it with polymer in a polar solvent, and delamination using shear force, the problems of aggregation and settlement of high concentration graphite dispersion liquid are solved, and long-term stable dispersion and high recovery rate are achieved.

JP2025038730APending Publication Date: 2025-03-19LEXI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145516
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the aggregation and settlement of pattern nanomaterials under high concentrations, and it is difficult to maintain long-term dispersion stability.

Method used

By mixing and grinding the graphite and organic acid salt in a dry or paste form, a composite of graphite and organic acid salt is formed and mixed with the dissolved polymer in a polar solvent, delamination of the graphite composite is applied to form graphite with a negative potential and positively charged modified graphite.

Benefits of technology

It effectively inhibits the aggregation and settlement of graphite, realizes the stability of high-concentration graphite dispersion, and improves the recovery rate of graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038730000001
    Figure 2025038730000001
  • Figure 2025038730000002
    Figure 2025038730000002
  • Figure 2025038730000003
    Figure 2025038730000003
Patent Text Reader

Abstract

To provide a method for producing a graphene dispersion liquid which suppresses coagulation and sedimentation of graphene that is easily coagulated and is a nanomaterial, can efficiently obtain a dispersion liquid having high concentration of the graphene, and can keep a dispersion state for a long period of time.SOLUTION: A method for producing a graphene dispersion liquid includes a step (A) of crushing graphite and an organic acid salt while mixing the substances in a paste state by a dry process, a step (B) of washing a mixture obtained in the step (A) with water, and obtaining a graphite composite body of the graphite and the organic acid salt, and a step (C) of mixing the graphite composite body and a dispersion solution in which a polymer is dissolved in a polar solvent while imparting shear force thereto, and delaminating the graphite composite body in the dispersion solution, wherein viscosity of the dispersion solution is 3.0 mPa s to 25.0 mPa s, and surface tension of the dispersion solution is 10 mN / m to 60 mN / m.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a graphene dispersion and a method for producing the same. [Background technology]

[0002] Graphene has excellent properties such as thermal conductivity, flexibility, and toughness, and is therefore being studied and applied in a variety of fields. However, because graphene is a nanomaterial, it tends to aggregate. Therefore, technology to improve the dispersibility of graphene is also important.

[0003] For example, Patent Document 1 discloses a method for producing an inorganic particle composite comprising: a step (A) of adding a water-soluble salt to an inorganic powder and mixing them in a dry or paste state; and a step (B) of washing with water after the step (A) to obtain an inorganic particle composite containing a component derived from the water-soluble salt, the water-soluble salt being selected from the group consisting of an inorganic particle composite having an acid dissociation constant pKa (H 2 A method for producing an inorganic particle composite in which the inorganic particle composite is a water-soluble salt in which O) is greater than 0 is disclosed, and graphene is described as one example of the inorganic particle composite. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-147713 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 describes that the inorganic particle composite obtained by the method described in Patent Document 1 has excellent dispersion stability when dispersed in a polar solvent such as acetone or water / propanol. However, Patent Document 1 does not fully consider dispersibility when the concentration of the inorganic particle composite in the polar solvent is high. The higher the concentration of graphene in a dispersion, the more likely it is to aggregate or settle, but from an industrial point of view, a dispersion with a high graphene concentration is required. Therefore, even when the graphene concentration is high, it has been required to suppress aggregation and settling and ensure dispersibility for a long period of time.

[0006] Under such circumstances, an object of the present invention is to provide a graphene dispersion that can suppress aggregation and precipitation of graphene, which is a nanomaterial that easily aggregates, efficiently obtain a dispersion having a high graphene concentration, and can maintain the dispersed state for a long period of time, and a method for producing the same. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors discovered that the following invention meets the above object, and thus completed the present invention.

[0008] That is, the present invention relates to the following inventions. <1> A method for producing a graphene dispersion, comprising: a step (A) of grinding graphite and an organic acid salt while mixing them in a dry state or in a paste state; a step (B) of washing the mixture obtained in the step (A) with water to obtain a graphite composite of the graphite and the organic acid salt; and a step (C) of mixing the graphite composite with a dispersion solution in which a polymer is dissolved in a polar solvent while applying a shear force, to exfoliate the graphite composite in the dispersion solution, wherein the viscosity of the dispersion solution is 3.0 mPa s to 25.0 mPa s and the surface tension of the dispersion solution is 10 mN / m to 60 mN / m. <2> The organic acid salt is a salt of an organic acid and a lithium ion. <1> A method for producing the graphene dispersion according to claim 1. <3> The organic acid salt is a citrate. <1> or <2> A method for producing the graphene dispersion according to claim 1. <4> The weight average molecular weight (Mw) of the polymer is 600,000 or more. <1> from <3> 13. The method for producing the graphene dispersion according to claim 12, <5> The polymer is a fluorine-based polymer, and the polar solvent is an amide-based solvent. <1> from <4> 13. The method for producing the graphene dispersion according to claim 12, <6> The mass ratio of the polymer to the polar solvent is 0.2 mass % to 1.0 mass %. <1> from <5> 13. The method for producing the graphene dispersion according to claim 12, <7> In the step (C), the graphite composite is mixed in an amount of 1 g to 50 g per 1 L of the dispersion solution. <1> from <6> 13. The method for producing the graphene dispersion according to claim 12, <8> A graphene dispersion comprising graphene having anionic sites bound with citric acid and modified graphene comprising cations, a polymer, and a polar solvent. Effect of the Invention

[0009] According to the present invention, there is provided a graphene dispersion that can suppress aggregation and precipitation of graphene, which is a nanomaterial that easily aggregates, efficiently obtain a dispersion having a high graphene concentration, and can maintain the dispersed state for a long period of time, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following is a detailed description of the embodiments of the present invention, but the following description of the constituent elements is one example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following content as long as the gist of the present invention is not changed. Note that in this specification, when the expression "~" is used, it is used as an expression including the numerical value or physical property value before and after it.

[0011] (Method of producing graphene dispersion) The present invention relates to a method for producing a graphene dispersion (hereinafter sometimes referred to as the "production method of the present invention") comprising: a step (A) of mixing graphite and an organic acid salt in a dry state or in a paste state and pulverizing them; a step (B) of washing the mixture obtained in the step (A) with water to obtain a graphite composite of the graphite and the organic acid salt; and a step (C) of mixing the graphite composite with a dispersion solution in which a polymer is dissolved in a polar solvent while applying a shear force, to exfoliate the graphite composite in the dispersion solution, wherein the dispersion solution has a viscosity of 3.0 mPa s to 25.0 mPa s and a surface tension of 10 mN / m to 60 mN / m.

[0012] One of the features of the manufacturing method of the present invention is that in step (C), the graphite composite obtained in step (B) is delaminated using a dispersion solution having a specific viscosity and surface tension. The graphite composite obtained in step (B) has anionic sites in which an organic acid is bound to the graphite and is negatively charged. Therefore, in step (C), it is considered that the graphene (i.e., graphene having anionic sites in which an organic acid is bound and modified graphene containing cations) produced by effective delamination of the graphite composite is dispersed due to electrostatic repulsion. At this time, by using a dispersion solution having specific physical properties, the graphite composite is easily delaminated, the graphene concentration can be increased, and the dispersion stability can be maintained for a long period of time even in a dispersion solution with a high graphene concentration. In addition, graphene can be recovered at a high recovery rate, such as 50% or more.

[0013] (Process (A)) In step (A), graphite and an organic acid salt are mixed in a dry state or in a paste form and pulverized. This causes a reaction between the graphite and a part of the organic acid salt, producing a graphite complex of the graphite and the organic acid salt. In this graphite complex of the graphite and the organic acid salt, the organic acid derived from the organic acid salt is bonded to the graphite, and cations derived from the organic acid salt are present in the vicinity of the anionic sites of the graphite to which the organic acid is bonded.

[0014] (graphite) The type of graphite is not particularly limited, and any of flake graphite, lump graphite, swollen graphite, amorphous graphite, artificial graphite, etc. is usable. From the viewpoint of facilitating the preparation of a dispersion in which thinner graphene is dispersed, flake graphite is preferably used.

[0015] (organic acid salt) The organic acid salt is a compound of an organic acid and a cation, and examples of the salt include an organic acid and an alkali metal ion such as sodium, potassium, or lithium; an alkaline earth metal ion such as calcium ion or magnesium ion; or an ammonium ion. Among these, it is preferable to use an organic acid lithium salt, which is a salt of an organic acid and a lithium ion. Specifically, examples of the salt include citrate, glutamate, acetate, and tartrate, and citrate is preferable, and lithium citrate is more preferable.

[0016] The graphite and the organic acid salt are mixed and ground in a dry state or in a paste state. Mixing in a paste state means mixing in a state where the viscosity is high but fluidity is recognized. Specifically, the viscosity of the mixture is 1 s at 20°C and a shear rate of 1 s -1 This means that the mixture is mixed at a viscosity of about 0.01 to 500 Pa·s.

[0017] The method of mixing and pulverization is not particularly limited, and known methods can be used, for example, a bead mill, a jet mill, a hammer mill, a high-speed stirrer, etc. The time for mixing and pulverization is not particularly limited, and can be, for example, about 10 minutes to 5 hours, 15 minutes to 4 hours, 30 minutes to 3 hours, or 45 minutes to 2 hours.

[0018] The mixing ratio of graphite to the organic acid salt can be, for example, 0.01 to 100 parts by mass, 0.1 to 10 parts by mass, or 0.5 to 5 parts by mass of the organic acid salt per 1 part by mass of graphite.

[0019] (Process (B)) Step (B) is a step of washing the mixture obtained in step (A) with water to obtain a graphite composite of graphite and an organic acid salt. The mixture obtained in step (A) contains unreacted organic acid salts in addition to the graphite composite produced by the reaction of graphite with the organic acid salt. The mixture obtained in step (A) is washed with water to remove the unreacted organic acid salts, thereby recovering a graphite composite of graphite and an organic acid salt (sometimes simply referred to as a "graphite composite"). The cation concentration of the obtained graphite composite is about 1 to 100,000 ppm, or about 35 to 10,000 ppm.

[0020] The mixture obtained in step (A) can be washed with water by mixing the mixture obtained in step (A) with water for a predetermined time, and then filtering to remove the water. The washing with water may be performed multiple times. There is no particular limit to the amount of water used, but it is preferable to add an excess amount of water to the mixture, such as 50 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more per part by mass of the mixture, each time.

[0021] (Process (C)) In step (C), the graphite composite obtained in step (B) is mixed with a dispersion solution in which a polymer is dissolved in a polar solvent while applying a shear force, and the graphite composite is delaminated in the dispersion solution. By step (C), a graphene dispersion is obtained in which graphene having anionic sites to which an organic acid is bonded and modified graphene containing cations are dispersed in the dispersion solution.

[0022] (Dispersion solution) The dispersion solution used in the step (C) is a solution in which a polymer is dissolved in a polar solvent, and has a viscosity of 3 mPa·s to 25 mPa·s and a surface tension of 10 mN / m to 60 mN / m.

[0023] (polymer) The polymer may be any polymer that can dissolve in a polar solvent and achieve the above-mentioned viscosity and surface tension. Among them, the polymer is preferably a polar polymer. It is considered that the use of a polar polymer can enhance the effect of peeling off graphene by electrostatic repulsion. The polymer may be one type or a combination of two or more types. Specifically, fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene; polyimide, etc. are included, and fluorine-based polymers are preferable, and polyvinylidene fluoride is more preferable. Polyvinylidene fluoride may be a homopolymer of vinylidene fluoride, or a copolymer of vinylidene fluoride and other monomers.

[0024] In addition, if the proportion of the polymer in the dispersion is too high, it may affect the physical properties of a product produced using the obtained graphene dispersion. Therefore, in the dispersion, the mass ratio of the polymer to the polar solvent (polymer mass / polar solvent mass×100(%)) is preferably 0.2% by mass to 1% by mass, more preferably 0.3% by mass to 0.8% by mass.

[0025] The polymer preferably has a weight average molecular weight (Mw) of 600,000 or more, more preferably 600,000 to 1,500,000, and even more preferably 800,000 to 1,200,000. The use of such a high molecular weight polymer is preferable because it is possible to achieve the above-mentioned viscosity and surface tension while reducing the amount of the polymer in the dispersion solution. The weight average molecular weight (Mw) can be determined by gel permeation chromatography (GPC).

[0026] (Polar Solvent) The polar solvent can be appropriately selected according to the type of polymer, and examples thereof include amide-based solvents such as N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, and N-methylcaprolactam; dimethylsulfoxide; ketone-based solvents such as acetone and methyl ethyl ketone; ether-based solvents such as tetrahydrofuran; nitrile-based solvents such as acetonitrile; water; and alcohol-based solvents such as ethanol, methanol, 2-propanol, butanol, and benzyl alcohol. These may be used alone or in combination of two or more. For example, when a fluorine-based polymer is used, it is preferable to use an amide-based solvent as the polar solvent, and it is more preferable to use N-methyl-2-pyrrolidone.

[0027] (viscosity) The viscosity of the dispersion solution is 3.0 mPa·s to 25.0 mPa·s. If the viscosity of the dispersion solution is less than 3.0 mPa·s, the peelability of the graphite composite decreases, and even if the layers are peeled off, it is difficult to maintain the interlayer distance, and the layers are easily re-aggregated, and about half or more of the graphite composite does not disperse. On the other hand, if the viscosity exceeds 25.0 mPa·s, the dispersion solution is difficult to enter between the layers of the graphite composite, and the dispersion solution absorbs shear force, making it difficult for the shear force to act on the graphite composite. The viscosity of the dispersion solution is preferably 3.5 mPa·s or more, more preferably 4.0 mPa·s or more, and even more preferably 5.0 mPa·s or more. The viscosity of the dispersion solution is preferably 20 mPa·s or less, more preferably 15 mPa·s or less, and even more preferably 10 mPa·s or less. Here, the viscosity of the dispersion solution is the viscosity measured at 20°C using an E-type viscometer.

[0028] (surface tension) The surface tension of the dispersion solution is 10 mN / m to 60 mN / m. If the surface tension of the dispersion solution is less than 10 mN / m, even if the graphite composite is peeled off, it is difficult to maintain the interlayer distance, and the graphite composite is likely to re-aggregate. On the other hand, if the surface tension exceeds 60 mN / m, the dispersion solution is difficult to penetrate between the layers of the graphite composite. The surface tension of the dispersion solution is preferably 20 mN / m or more, more preferably 30 mN / m or more, and even more preferably 35 mN / m or more. The surface tension of the dispersion solution is preferably 55 mN / m or less, more preferably 50 mN / m or less, and even more preferably 45 mN / m or less. Here, the surface tension of the dispersion solution is the surface tension measured at 20°C using a capillary rise type surface tensiometer.

[0029] The mixing ratio of the dispersion solution and the graphite composite is not particularly limited, and for example, the mass of the graphite composite per 1 L of the dispersion solution can be 1 g or more, 5 g or more, 10 g or more, 15 g or more, 20 g or more, etc. In the production method of the present invention, even in the case of a high concentration, the graphite composite can be dispersed while suppressing aggregation and precipitation, so the mass of the graphite composite per 1 L of the dispersion solution is preferably 5 g or more, more preferably 10 g or more, and even more preferably 15 g or more. On the other hand, since there is a limit to the effect of suppressing aggregation and precipitation, it is preferable to set an upper limit and manage the mass of the graphite composite per 1 L of the dispersion solution to be 50 g or less or 40 g or less.

[0030] Examples of the method of mixing while applying a shear force include ultrasonic treatment in which the mixture is stirred while irradiating ultrasonic waves, and pulverization treatment using a bead mill, jet mill, hammer mill, high-speed stirrer, etc. During mixing, it is necessary to control the temperature of the dispersion, and the temperature of the dispersion is usually controlled to about -5°C to 50°C. The temperature of the dispersion during mixing is preferably 0°C to 30°C.

[0031] The mixing time is appropriately selected depending on the mixing method, etc., but in the case of ultrasonic treatment, the treatment time can be, for example, about 5 minutes to 5 hours, 10 minutes to 4 hours, 30 minutes to 3 hours, or 45 minutes to 2 hours.

[0032] The liquid stirred while applying a shear force can be used as it is as a graphene dispersion liquid. Alternatively, after stirring while applying a shear force, centrifugal separation may be performed to remove particles with a large particle size and to improve dispersibility.

[0033] According to the manufacturing method of the present invention, a graphene dispersion containing modified graphene, a polymer, and a polar solvent can be easily obtained. The modified graphene is obtained by delaminating a graphite composite containing an anionic site to which an organic acid derived from an organic acid salt is bonded and a cation derived from an organic acid salt, and contains graphene having an anionic site to which an organic acid is bonded and a cation. In the modified graphene, an organic acid is bonded to a carbon atom on the surface of the graphene, and the organic acid is negatively charged to form an anionic site, and it is considered that a counter cation is present in the vicinity of the anionic site. At least a part of the functional group of the organic acid bonded to the graphene may be in the form of an ion. The graphene having an anionic site to which an organic acid is bonded is a multilayer or single layer, and the average particle size is preferably 1000 nm or less. The bond between the graphene and the organic acid may be any of a covalent bond, an ionic bond, and a coordinate bond. The cation of the modified graphene is a cation derived from the organic acid salt used in step (A) that forms a pair with the anionic site of the graphene.

[0034] The graphene dispersion produced by the production method of the present invention is mainly composed of modified graphene, a polymer, and a polar solvent, and the ratio of the total amount of the modified graphene, the polymer, and the polar solvent in the graphene dispersion can be 80 mass% or more, 90 mass% or more, 95 mass% or more, 98 mass% or more, 99 mass% or more, etc. In addition, the graphene dispersion may be substantially composed of the modified graphene, the polymer, and the polar solvent. It is preferable that the graphene dispersion does not contain any components other than the modified graphene, the polymer, and the polar solvent, except for unavoidable impurities.

[0035] Specifically, by using a citrate salt as the organic acid salt in step (A), it is possible to obtain a graphene dispersion containing graphene having an anionic site to which citric acid is bound, modified graphene containing a cation, a polymer, and a polar solvent. Also, by using a salt of citric acid and an alkali metal ion as the organic acid salt in step (A) and a fluorine-based polymer as the polymer in step (C), it is possible to obtain a graphene dispersion containing graphene having an anionic site to which citric acid is bound, modified graphene containing an alkali metal ion, a fluorine-based polymer, and a polar solvent.

[0036] The manufacturing method of the present invention can obtain a dispersion having a high concentration of modified graphene. For example, the manufacturing method of the present invention can obtain a graphene dispersion having a concentration of modified graphene of 5 g / L to 50 g / L, 10 g / L to 48 g / L, 15 g / L to 46 g / L, or 20 g / L to 45 g / L. Even graphene that is prone to aggregation and has an average particle size of 1000 nm or less can be dispersed at such a concentration and the dispersed state can be maintained well for a long period of time. EXAMPLES

[0037] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.

[0038] [material] The graphite used was flake graphite (Ito Graphite Industries Co., Ltd., CNP15). Lithium citrate, potassium citrate, potassium carbonate, and N-methyl-2-pyrrolidone (NMP) were purchased from Kishida Chemical Co., Ltd. The polymer used was polyvinylidene fluoride (PVdF) (Kureha Corporation, homopolymer #7300, Mw: 1 million or more).

[0039] [Example 1] (Example 1-1) ·Process (A) At room temperature in air, 1 g of flake graphite and 2 g of lithium citrate were mixed for 30 minutes at a rotation speed of 500 rpm using a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S).

[0040] ·Process (B) 200 g of water was added to the mixture obtained in step (A), stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid collected by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. The obtained solid was used in step (C) as a graphite composite of graphite and lithium citrate (composite (GR)).

[0041] ·Process (C) A dispersion solution was prepared by dissolving 500 mg of polyvinylidene fluoride in 100 g of N-methyl-2-pyrrolidone (NMP). The complex (GR) and the dispersion solution were mixed so that the concentration of the complex (GR) was 1 g / L (1 g of the complex (GR) obtained in step (B) per 1 L of the dispersion solution), and ultrasonic treatment was performed for 15 minutes while controlling the temperature of the dispersion solution to be 0°C to 30°C, followed by centrifugation (1,000 G, 4 minutes) to obtain a graphene dispersion solution.

[0042] (Examples 1-2 to 1-3, Comparative Example 1-1) A graphene dispersion was obtained in the same manner as in Example 1-1, except that the amount of polyvinylidene fluoride dissolved in 100 g of NMP was set as shown in Table 1.

[0043] [evaluation] (Viscosity and surface tension of dispersion solution) The viscosity of the dispersion solution was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., model number: TV-100H, standard cone rotor) at 20°C and a shear rate of 100 S. -1 The surface tension of the dispersion solution was measured at 20° C. using a capillary rise type surface tensiometer (DG-1, manufactured by Hyomen Sokki Seisakusho). The measurement results are shown in Table 1.

[0044] (Graphene dispersion concentration) A predetermined amount of the graphene dispersion was collected and completely dried at 100°C, and then the mass (g) of the residue was measured. The mass (g) of PVdF in the collected graphene dispersion was calculated from the concentration of PVdF, and the graphene dispersion concentration (concentration of modified graphene in the graphene dispersion) (g / L) was calculated from "(mass (g) of the residue - mass (g) of PVdF) / collected amount (L)". Table 1 shows the graphene dispersion concentrations of the graphene dispersions obtained in Examples 1-1 to 1-3 and Comparative Example 1-1.

[0045] [Table 1]

[0046] [Example 2-1] ·Process (A) At room temperature in air, 1 g of flake graphite and 2 g of lithium citrate were mixed for 60 minutes at a rotation speed of 500 rpm using a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S).

[0047] ·Process (B) 200 g of water was added to the mixture obtained in step (A), stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid recovered by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. The obtained solid was used as the composite (GR) in step (C).

[0048] ·Process (C) A dispersion solution was prepared by dissolving 200 mg of polyvinylidene fluoride in 100 g of NMP. The composite (GR) and the dispersion solution were mixed so that the concentration of the composite (GR) was 1 g / L, and ultrasonic treatment was performed for 60 minutes while controlling the temperature of the dispersion solution to be 0°C to 30°C, followed by centrifugation (1,000 G, 4 minutes) to obtain a graphene dispersion solution.

[0049] (Recovery rate) The graphene dispersion concentration was obtained and the mass of graphene in the graphene dispersion was calculated in the same manner as in Example 1. The recovery rate was calculated by dividing the mass (g) of graphene in the graphene dispersion by the mass (g) of the composite (GR) used in step (C), and the recovery rate was 91%.

[0050] (dispersion stability) Immediately after step (C), after standing for 68 hours, and after standing for 168 hours, a few mL of the graphene dispersion was sampled. The sampled solution was dried to completely remove the solvent in the sampled solution, and the mass of the remaining solid was measured to determine the graphene dispersion concentration in the sampled solution. As a result, the graphene dispersion concentration in each of the graphene dispersions immediately after step (C), after standing for 68 hours, and after standing for 168 hours was the same.

[0051] [Examples 2-2 to 2-3] A graphene dispersion was obtained in the same manner as in Example 2-1, except that the concentration of the composite (GR) (the amount (g) of the composite (GR) per 1 L of the dispersion solution) was changed as shown in Table 2. Table 2 shows the recovery rate in each example.

[0052] [Table 2]

[0053] [Comparative Examples 2-1 to 2-4] A graphene dispersion was obtained in the same manner as in Example 2-1, except that in step (C), NMP (without addition of PVdF) was used instead of the dispersion solution, and the concentration of the composite (GR) (amount (g) of the composite (GR) relative to 1 L of NMP) was set as shown in Table 3. Table 3 shows the recovery rate in each comparative example. The viscosity of NMP was 1.9 mPa·s and the surface tension was 39 mN / m.

[0054] [Table 3]

[0055] [Examples 3-1 to 3-3] ·Process (A) At room temperature in air, 1 g of flake graphite and 2 g of lithium citrate were mixed for 60 minutes at a rotation speed of 500 rpm using a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S).

[0056] ·Process (B) 200 g of water was added to the mixture obtained in step (A), stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid recovered by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. The obtained solid was used as the composite (GR) in step (C).

[0057] ·Process (C) A dispersion solution was prepared by dissolving 500 mg of polyvinylidene fluoride in 100 g of NMP. The composite (GR) and the dispersion solution were mixed, and ultrasonic treatment was performed for 60 minutes while controlling the temperature of the dispersion solution to be 0°C to 30°C. Then, centrifugation (1,000G, 4 minutes) was performed to obtain graphene dispersion solutions with graphene concentrations of 20 g / L, 10 g / L, and 1 g / L.

[0058] [Comparative Examples 3-1 to 3-3] A graphene dispersion was obtained in the same manner as in Examples 3-1 to 3-3, except that NMP (without the addition of PVdE) was used instead of the dispersion solution in step (C).

[0059] [evaluation] The obtained graphene dispersion was allowed to stand for a predetermined time, and the graphene dispersion concentration at the predetermined time was measured in the same manner as in Example 2-1 to evaluate the dispersion stability. The results are shown in Table 4. In Table 4, the graphene dispersion concentration after standing for a predetermined time is a relative value when the graphene dispersion concentration at the time of standing for 0 is set to 1.

[0060] [Table 4]

[0061] [Reference example] At room temperature and in air, the materials shown in Table 5 were added to a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S) and processed at a rotation speed of 500 rpm for 30 minutes. Next, 200 g of water was added, stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid recovered by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. NMP was mixed so that the concentration of the graphite or graphite composite recovered by filtration became 1 g / L, and ultrasonic treatment was performed for 15 minutes while controlling the temperature of the dispersion to 10 to 30 ° C., and then centrifugation (1,000 G, 4 minutes) was performed to obtain a graphene dispersion. Table 5 shows the graphene concentrations in the obtained graphene dispersions.

[0062] [Table 5]

Claims

1. A step (A) of grinding graphite and an organic acid salt while mixing them in a dry state or in a paste state; a step (B) of washing the mixture obtained in the step (A) with water to obtain a graphite composite of graphite and an organic acid salt; (C) mixing the graphite composite with a dispersion solution in which a polymer is dissolved in a polar solvent while applying a shear force, thereby exfoliating the graphite composite in the dispersion solution; having The method for producing a graphene dispersion, wherein the dispersion has a viscosity of 3.0 mPa·s to 25.0 mPa·s and a surface tension of 10 mN / m to 60 mN / m.

2. The method for producing a graphene dispersion according to claim 1 , wherein the organic acid salt is a salt of an organic acid and a lithium ion.

3. The method for producing a graphene dispersion according to claim 1 or 2, wherein the organic acid salt is a citrate.

4. The method for producing a graphene dispersion according to claim 1 or 2, wherein the polymer has a weight average molecular weight (Mw) of 600,000 or more.

5. the polymer is a fluorine-based polymer, The method for producing a graphene dispersion according to claim 1 or 2, wherein the polar solvent is an amide-based solvent.

6. 3. The method for producing a graphene dispersion according to claim 1, wherein a mass ratio of the polymer to the polar solvent is 0.2 mass% to 1.0 mass%.

7. 3. The method for producing a graphene dispersion according to claim 1, wherein in the step (C), the graphite composite is mixed in an amount of 1 g to 50 g per 1 L of the dispersion solution.

8. A graphene dispersion comprising graphene having anionic sites bound with citric acid and modified graphene comprising cations, a polymer, and a polar solvent.

Citation Information

Patent Citations

  • Inorganic particle composite, production method thereof, and inorganic particle composite dispersion

    JP2019147713A